Teplárenské zdroje v ČR - Bártová, Jana (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Tato bakalářská práce se zabývá teplárenskými zdroji v České republice. Součástí práce je rozdělení a popis tepláren, sloužících k výrobě nejen tepelné, ale i elektrické energie. V další části práce jsou popsány výhody a nevýhody centrálního zásobování teplem a individuálního vytápění. Poslední část práce obsahuje statistické zpracování teplárenských zdrojů nacházejících se v České republice.

This bachelor thesis deals with thermal recources in the Czech Republic. The first part of the work is about the division and description of heating plants used for the production of thermal and electric energy. The second part of the thesis describes the advantages and disadvantages of district heating and individual heating. The last part of my work contains statistical processing of heat sources located in the Czech Republic.
Source for heat production in the Czech Republic
Keywords: teplárna; turbína; centrální zásobování teplem; tepelná energie; KVET; heating plant; turbine; district heating; thermal energy; KVET